Prevalence of Inflammatory Bowel Disease in an Insured Population in Puerto Rico During 1996 - Torres, Esther A.; De Jesús, Ramón; Pérez, Cynthia M.; Iñesta, Michael; Torres, Daniel; Morell, Carlos; Just, Erica (Puerto Rico Health Sciences Journal, 2011)
see manuscript